2011
DOI: 10.1590/s0100-06832011000400006
|View full text |Cite
|
Sign up to set email alerts
|

Microbial biomass and soil chemical properties under different land use systems in northeastern Pará

Abstract: SUMMARYThe increase in agricultural production in the Brazilian Amazon region is mostly a result of the agricultural frontier expansion, into areas previously influenced by humans or of native vegetation. At the same time, burning is still used to clear areas in small-scale agricultural systems, leading to a loss of the soil productive capacity shortly after, forcing the opening of new areas. This study had the objective of evaluating the effect of soil preparation methods that involve plant residue shredding,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
1
9
0
3
Order By: Relevance
“…The values for SMBC and SMBN agreed with results of earlier studies conducted in the same region (Rangel-Vasconcelos et al, 2005;Sotta et al, 2008;Lopes et al, 2011;Melo et al, 2012). Bittencourt et al (2006) found a higher SMBN content in Amazonian soils under secondary vegetation in the rainy season.…”
Section: Discussionsupporting
confidence: 88%
“…The values for SMBC and SMBN agreed with results of earlier studies conducted in the same region (Rangel-Vasconcelos et al, 2005;Sotta et al, 2008;Lopes et al, 2011;Melo et al, 2012). Bittencourt et al (2006) found a higher SMBN content in Amazonian soils under secondary vegetation in the rainy season.…”
Section: Discussionsupporting
confidence: 88%
“…Nitrogênio mineral e microbiano do solo em sistemas agroflorestais com palma de óleo na Amazônia oriental Em geral, os valores de C orgânico e N total foram consistentes com valores obtidos em outros estudos realizados na Amazônia Oriental (Desjardins et al 2004;Silva et al 2006;Lopes et al 2011). A semelhança entre os tipos de vegetação quanto a concentração de N e relação C/N do solo, e a maior concentração de C no solo sob o SAF com alta diversidade de espécies em relação à floresta secundária, evidenciam o caráter conservacionista do solo dos sistemas de produção de palma de óleo avaliados.…”
Section: Discussão C Orgânico N Total E Relação C/n Do Solounclassified
“…O percentual médio de N imobilizado pela microbiota do solo (N mic :N tot ), na época chuvosa, foi elevado (acima de 13%), o que não é incomum em solos tropicais. Gama-Rodrigues et al (2005) registraram valores de N mic :N tot próximos de 20% no final da época chuvosa, enquanto Lopes et al (2011) relataram valores acima de 48% em SAFs sucessionais na Amazônia Oriental.…”
Section: Discussão C Orgânico N Total E Relação C/n Do Solounclassified
“…The highest MBN concentration occurred in the NT-8 area and was potentially related to N immobilization in the soil (Lopes et al, 2011) because of high levels of OM. The continuous deposition of OM by no-tillage systems favors increases in OM, OM conservation, and the gradual release of nutrients based on the mineralization rate (Santiago et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The environmental stress conditions, such as acidity, temperature, elevated heavy metal contents, soil compaction, or low OC nutritional quality, reduce the efficiency of the microbial biomass and MBN (Lopes et al, 2011), which results in a low MBN/Total N ratio. In highly weathered soils with high acidity and low pH, such as those in the study area, CO undergoes rapid decomposition and mineralization, which results in a low soil nutrient supply.…”
Section: Resultsmentioning
confidence: 99%